Non-invasive methods for diagnosing portal hypertension and variceal bleeding due to liver cirrhosis secondary to NAFLD/MASLD: systematic review - Nebyu Yonas Shanka; Nebyu Yonas Shanka; Chavdar S. Pavlov; Nigatu Leul Mekonnen (Frontiers in Medicine)
BackgroundNon-alcoholic fatty liver disease (NAFLD), recently re-termed as metabolic dysfunction-associated steatotic liver disease (MASLD), is a global health concern affecting approximately 25% of adults. Complications such as portal hypertension and variceal bleeding are critical to diagnose but challenging with traditional invasive methods like hepatic venous pressure gradient (HVPG) measurement and esophagogastroduodenoscopy (EGD), which are not always feasible and carry risks.ObjectivesThis systematic review aim to evaluate the diagnostic accuracy of non-invasive methods for diagnosing portal hypertension and variceal bleeding in patients with NAFLD/MASLD cirrhosis, comparing these methods to invasive standards.MethodsA comprehensive literature search was conducted across PubMed, Cochrane Library, Google Scholar, and ScienceDirect from January 2000 to May 2024. Studies included evaluated non-invasive diagnostic techniques for portal hypertension and variceal bleeding, compared with HVPG and EGD, focusing on adult patients with confirmed NAFLD/MASLD cirrhosis. Data extraction covered study characteristics and diagnostic accuracy metrics. The quality of studies was assessed using the QUADAS-2 tool. Meta-analyses were performed using R and Python.ResultsEleven studies involving 2,707 patients met the inclusion criteria. Liver stiffness measurement (LSM) via transient elastography demonstrated high sensitivity (85%) and specificity (79%) for diagnosing clinically significant portal hypertension (CSPH) at a 20 kPa cutoff. For severe portal hypertension (SPH), LSM had a sensitivity of 81% and specificity of 85% at 25 kPa. Combining LSM with platelet count resulted in a sensitivity of 97% but lower specificity (41%) for CSPH. Spleen stiffness measurement (SSM) also showed good diagnostic performance with a sensitivity of 89% and specificity of 75% for CSPH.ConclusionNon-invasive tests, particularly LSM and SSM, show promise in diagnosing portal hypertension and variceal bleeding in NAFLD/MASLD cirrhosis. These methods offer high sensitivity, especially in combination, supporting their use in clinical settings to potentially reduce the need for invasive procedures. Future research should aim to standardize protocols and explore additional biomarkers to further enhance diagnostic accuracy.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?, identifier CRD42024567024.